If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 6xy = 35 Solving X + 6xy = 35 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6xy' to each side of the equation. X + 6xy + -6xy = 35 + -6xy Combine like terms: 6xy + -6xy = 0 X + 0 = 35 + -6xy X = 35 + -6xy Simplifying X = 35 + -6xy
| 100x^2+1=101 | | 3(c+2)+5(c-5)= | | A-(-92)=2 | | 6[2]+2[y]=12 | | 7m+4=-1+6m | | (X-.6)/X=.78 | | n/9x3/4=8 | | 6[0]+2[y]=12 | | 2m^2+m-6=0 | | 9=-3+4w | | -4w+2+5w=-4+5 | | 35-8a=7(6a-3) | | 6[-2]+2[y]=12 | | 60x=5x+10 | | -23=x/3-8 | | a+ab+abc+abcd=1c*c*5 | | 3.25x+1.5y=15 | | 35=-3+5(n+7) | | 7x^2-3w-9=0 | | Px^2+(2p-q)x-2q=0 | | 6+0.5x=20 | | -35x^2-140+420=0 | | 0.5p=q-2 | | S/3—4=2 | | -6=t/13 | | 4(p+3)+4(p-6)= | | 20x+5-9x-2=40 | | -9z+3z=23 | | -p-4=2q | | a+ab+abc+abcd=1*c*c*5 | | 29-[5+7y-2(y+2)]=-5(5y-6)-[8(y-1)-21y+24] | | (a+5)(a+5)(a+5)= |